Implementation of Career Development Policy for Civil Servants Through Talent Mobility in Dki Jakarta Provincial Social Services - Dhita, Resti Sandya; Amalia, Rizki (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2023)
In accordance with PANRB Ministerial Regulation Number 3 of 2020, National ASN Talent Management is an integral component of National Career Development Management, executed through transfers and/or promotions. The DKI Jakarta Provincial Social Service, housing a staff of 200 employees, reveals that approximately 18.5 percent, or 47 employees, have not undergone rotations in over 5 years. This study seeks to assess the application of civil servant career development policies via Talent Mobility within the DKI Jakarta Provincial Social Service. Employing a qualitative descriptive research method with an inductive approach, the research delves into the implementation of these policies by scrutinizing the factors connecting policy to performance. The findings indicate a reasonably effective implementation of the civil servant career development policy through Talent Mobility in the DKI Jakarta Provincial Social Service. However, certain aspects, such as standard factors and policy objectives, policy resources, inter-organizational communication and law enforcement activities, characteristics of implementing agencies, economic, social, and political conditions, and the disposition of implementers, warrant improvement. Recommendations stemming from the research are as follows: (1) Emphasize the need for commitment from all stakeholders in executing the talent mobility policy, (2) Prioritize the analysis of employee needs before recruitment processes to ensure a more accurate alignment with organizational requirements, (3) Initiate formal outreach programs dedicated to discussing talent mobility to deepen employee understanding and engagement, (4) Establish a structured training program aligned with employees' respective fields of work, backed by a designated budget for training initiatives, (5) Institute programs aimed at enhancing employee welfare comprehensively, and (6) Recognize the pivotal role, particularly that of leaders, in reshaping employee thought patterns to align with the objectives of Talent Mobility.